2019
DOI: 10.1038/s41598-019-48550-1
|View full text |Cite
|
Sign up to set email alerts
|

Time and space scattered volcanism of Mt. Etna driven by strike-slip tectonics

Abstract: High-resolution seismic reflection, magnetic and gravity data, acquired offshore of Etna volcano, provide a new insight to understanding the relationship between tectonics and spatial-temporal evolution of volcanism. The Timpe Plateau, a structural high pertaining to the Hyblean foreland domain, located offshore of southeastern Mt. Etna, is speckled by volcanics and strongly affected by strike-slip tectonics. Transpressive deformation produced a push-up and a remarkable shortening along WNW-ESE to NW-SE trendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 64 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…However, the trace of the buried fault in the coastal area from Acitrezza to Acireale is well constrained within the very narrow corridor separating the outcrops of the downthrown Acireale lavas, to the northeast, and the raised marly‐clay succession of the Acitrezza ridge, to the southwest (Figure 2). This structure also extends offshore, where it is well imaged in seismic lines parallel to the Ionian coast (Firetto Carlino et al., 2019). These seismic lines show a NE‐facing normal fault with offset of the lava horizons and sedimentary substratum comparable to that constrained by geological and geophysical data onshore.…”
Section: Geological Settingmentioning
confidence: 84%
See 1 more Smart Citation
“…However, the trace of the buried fault in the coastal area from Acitrezza to Acireale is well constrained within the very narrow corridor separating the outcrops of the downthrown Acireale lavas, to the northeast, and the raised marly‐clay succession of the Acitrezza ridge, to the southwest (Figure 2). This structure also extends offshore, where it is well imaged in seismic lines parallel to the Ionian coast (Firetto Carlino et al., 2019). These seismic lines show a NE‐facing normal fault with offset of the lava horizons and sedimentary substratum comparable to that constrained by geological and geophysical data onshore.…”
Section: Geological Settingmentioning
confidence: 84%
“…Current volcano‐tectonic models of Mount Etna in eastern Sicily, Italy (Figure 1) are mostly based on geometric and kinematic analyses of the ground effects due to active deformation (e.g., coseismic fracturing and creep; Acocella & Neri, 2005; Azzaro, 1999; Azzaro et al., 2012; 2017; Rasà et al., 1996) in combination with geodetic data (GPS velocities and DInSAR interferograms; Azzaro et al., 2013; Bonforte & Puglisi, 2006; Bonforte et al., 2011; 2013; Palano, 2016; Murray et al., 2018), seismological information (Alparone et al., 2011, 2015; Cocina et al., 1997), and off‐shore seismic line interpretation (Argnani et al., 2013; Chiocci et al., 2011; Firetto Carlino et al., 2019; Gross et al., 2016; Polonia et al., 2016). The results of these studies emphasize the short‐period gravitational processes that actually obscure the volcano‐tectonic and regional tectonic signals of crustal deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The feedback loop involving magma intrusion, seaward sliding of Etna's east flank (Urlaub et al, 2018) and tectonic forces (Carlino et al, 2019) may have led to the features observed in the geophysical data encompassing the December 2018 eruption. In particular, the Okada (1992) model, which accounts for the deformation effect arising from a tensile fault, allows matching the horizontal deformation but fails to explain the vertical component of the deformation field (Figures 2b and 3c).…”
Section: Discussionmentioning
confidence: 99%
“…A fault segment clearly crops out at the Lachea Islet (Figure 1a). Some authors [29][30][31], mostly based on offshore data, assign great importance to this fault, inferring its continuation towards the Ionian abyssal plain.…”
Section: Geological Frameworkmentioning
confidence: 99%